A Fourier-transform infrared and laser-Raman spectroscopic investigation of 4,4′-bipyridyl-transition metal(II) tetracyanonickelate clathrates - Davies, J. Eric D.; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (My University, 1996)
The FT-IR and Raman spectra are reported of M(4,4-bipyridyl)Ni(CN)4nG (where M = Mn, Fe, Co, Cu or Zn and G = benzene or aniline;n = 0–2) clathrates. The host structure consists of a three-dimensional rigid lattice formed by infinite polymeric layers of {M-Ni(CN)4} and 4,4-bipyridyl bridges between the metal (M) atoms of the adjacent polymeric layers. Bidentate 4,4-bipyridyl molecules are found to be centrosymmetric in the structure.